2022
DOI: 10.48550/arxiv.2208.08499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Every graph is eventually Turán-good

Abstract: Let H be a graph. We show that if r is large enough as a function of H, then the r-partite Turán graph maximizes the number of copies of H among all K r+1 -free graphs on a given number of vertices. This confirms a conjecture of Gerbner and Palmer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We can deal with counting multiple graphs at the same time if the same graph is extremal for each of them, in particular if the same graph is extremal for each subgraphs of H. Two examples of this are counting linear forests if F has a color-critical edge [7], and counting any graph H if F has a color-critical edge and chromatic number at least 300|V (H)| 9 +1 [15,11].…”
Section: Results and Proofsmentioning
confidence: 99%
“…We can deal with counting multiple graphs at the same time if the same graph is extremal for each of them, in particular if the same graph is extremal for each subgraphs of H. Two examples of this are counting linear forests if F has a color-critical edge [7], and counting any graph H if F has a color-critical edge and chromatic number at least 300|V (H)| 9 +1 [15,11].…”
Section: Results and Proofsmentioning
confidence: 99%
“…The quantities ex(n, H, F ) and mex(m, H, F ) have motivated many interesting results; see [5,6,11,12,13,20] for an (incomplete) sample. However, these problems often stretch the notion of "easily measurable" properties on which extremal graph theory is based.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Morrison, Nir, Norin, Rzążewski and Wesolek [12] showed that for any graph H and large enough r, the maximum number of copies of H in a K r -free n-vertex graph is obtained by the Turán graph T r−1 (n), the balanced blow-up of K r−1 . In other words, the above conjecture works if r is enough large comparing to χ(H).…”
mentioning
confidence: 99%